The Lost City - Bullock, Sandra; Tatum, Channing; Pitt, Brad; Radcliffe, Daniel; Harrison, Patti; Nuñez, Oscar; Randolph, Da'Vine Joy; Lee, Raymond; Forbes-Johnson, Thomas; Anibal, Hector ([UNITED STATES] : Paramount, 2022)
Reclusive author Loretta Sage writes about exotic places in her popular adventure novels that feature a handsome cover model named Alan. While on tour promoting her new book with Alan, Loretta gets kidnapped by an eccentric billionaire who hopes she can lead him to an ancient city's lost treasure from her latest story. Determined to prove he can be a hero in real life and not just on the pages of her books, Alan sets off to rescue her.
"Bullock and Tatum are screwball gold together. Neither are ever too vain for the bit, and she especially gets to show off her skills as a physical comedian."--Associated Press
"The poster made it look kind of fun, and lo and behold, it is."--Los Angeles Times
"...if you need to lose yourself for an hour or two, it could be just the thing."--Time Magazine
07/26/2022
New DVD 2022 Summer.
Director, Aaron Nee, Adam Nee.
Sandra Bullock, Channing Tatum, Brad Pitt, Daniel Radcliffe, Patti Harrison, Oscar Nunez, Da'Vine Joy Randolph, Raymond Lee, Thomas Forbes-Johnson, Hector Anibal.
MPAA rating: PG-13.
DVD.
Keywords: Action / Adventure; Comedy; Adventure